Pengembangan Sistem Deteksi dan Pencegahan Deepfakes Pada Windows: Keamanan Distribusi Konten - Alif, Muh.; Hamuddin, Humaera; Rahman, Rakhmadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Deepfakes detection and prevention systems are needed nowadays. The publication of content made from AI manipulation is a threat in the digital world. This system is used to minimize the distribution of content that can be used by certain individuals to bring down a person or group. The detection carried out focuses on machine learning as the main system. Blockchain as a system that performs storage and verification based on comparing the original content that has been loaded with content that is considered manipulated. It is transparent and has various advantages that provide security for data and users. With the appropriate dataset in machine learning, detection can be done as needed. Machine learning does not reject many datasets to train the model created to be smarter in detection. Deeepfakes pose a significant threat to information dissemination. It is necessary to do good and correct prevention and detection so that disinformation does not occur and also so that there is no hoax information.